Influence of fuel additive in the formulation and combustion characteristics of water-in-diesel nanoemulsion fuel - Bidita, B. S.; Abdul Rashid, Suraya; Shehzad, Muhammad Arslan; Mohd Salleh, Mohamad Amran; Idris, Azni (American Chemical Society, 2014)
A comprehensive experimental study was accomplished to assess the influence of fuel additive in the formulation of water-in-diesel (W/D) nanoemulsions using surfactant in two ways, with and without including fuel additive, and a comparison is made with neat diesel. A range of surfactant concentration (0.25% to 0.40% v/v) was used with varying water concentration (0.7% to 1% v/v) to prepare W/D nanoemulsion fuel. High energy emulsification process was employed for this purpose and attempts to compare between both ways, physical and experimental observations were considered. The destabilization methods, mainly Oswald ripening, was discussed to investigate the stability. The influence of fuel additive over the characteristics of nanoemulsion such as droplet size, stability, viscosity, emulsion calorific value was studied in detail. The droplet size of W/D nanoemulsion fuel was found to be in the range approximately from 2 to 200 nm in both procedures. The engine test bed was utilized to combust the emulsion at the speed of 2600 rpm using power 2.2 KW with 50% load in order to investigate the brake specific fuel consumption (BSFC), brake thermal efficiency, exhaust mass flow rate, exhaust gas temperatures, emission gases concentrations such as carbon dioxide (CO2), carbon monoxide (CO), ammonia (NH3), and nitrogen oxides (NOx). It has been noted that the W/D nanoemulsion including fuel additive is able to considerably reduce the BSFC and exhaust mass flow rate compared to neat diesel. Brake thermal efficiency was increased by using W/D nanoemulsion including fuel additive. In addition, exhaust emissions of CO2, NH3, and NOx have been reduced using fuel additive mixed W/D nanoemulsion fuel. In contrast to the neat diesel, W/D nanoemulsion offered significantly less exhaust temperature and emission gas concentrations. The comprehensive study of the emission results recommends that the potential W/D nanoemulsions can be considered as an alternative to the conventional diesel fuel in order to reduce the environmental contaminations.